2020
DOI: 10.1002/smll.202001103
|View full text |Cite
|
Sign up to set email alerts
|

Design of Magnetic‐Plasmonic Nanoparticle Assemblies via Interface Engineering of Plasmonic Shells for Targeted Cancer Cell Imaging and Separation

Abstract: decade, many approaches for synthesizing multifunctional NPs with combined properties have been developed, such as heterogeneous crystal growth, [3][4][5] coassembly of different building blocks, [6,7] and the template-based method involving chemical and/or physical binding. [8,9] In particular, the template-based method is advantageous for utilizing the size-and shape-dependent properties of individual NPs, [8][9][10] new properties resulting from inter-particle coupling, [8,10,11] and independently additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 56 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…Medical imaging techniques have evolved very quickly over the past 20 years, overall in cancer disease, to identify very little tumor masses for an early diagnosis (Kumar et al, 2019;Li et al, 2019c;Vaidya et al, 2019). This evolution has occurred through the combined use of classical imaging techniques (like MRI, PET and SPECT) with NPs (Forte et al, 2019;Song et al, 2020) and advancing toward the use of innovative imaging techniques like photoacoustic (PA), surface-enhanced Raman scattering (SERS), and near infrared light up-conversion (NIR-Up) (Silvestri et al, 2019;Ge et al, 2020;Kim et al, 2020). All these techniques are very useful in combination with NPs-mediated delivery in order to accumulate CAs in the tissues of interest.…”
Section: The Role Of Nanoparticles In Cancer Diseasementioning
confidence: 99%
“…Medical imaging techniques have evolved very quickly over the past 20 years, overall in cancer disease, to identify very little tumor masses for an early diagnosis (Kumar et al, 2019;Li et al, 2019c;Vaidya et al, 2019). This evolution has occurred through the combined use of classical imaging techniques (like MRI, PET and SPECT) with NPs (Forte et al, 2019;Song et al, 2020) and advancing toward the use of innovative imaging techniques like photoacoustic (PA), surface-enhanced Raman scattering (SERS), and near infrared light up-conversion (NIR-Up) (Silvestri et al, 2019;Ge et al, 2020;Kim et al, 2020). All these techniques are very useful in combination with NPs-mediated delivery in order to accumulate CAs in the tissues of interest.…”
Section: The Role Of Nanoparticles In Cancer Diseasementioning
confidence: 99%
“…The deposition of a Ag 0 monolayer on specific Au facets via UPD inhibits or slows the deposition of Au onto these facets, while Au growth occurs on other facets. According to another mechanism, the reduction of Au ions to Au 0 leaves many Cl ions in solution. , In the presence of Ag ions, AgCl precipitates on the surface of the growing AuNPs, thereby blocking those surface sites. , The final result of both mechanisms is that certain Au surface sites are blocked from Au growth by precipitated Ag, either in the form of a Ag 0 monolayer or as AgCl, thus leading to the anisotropic in situ growth of the AuNPs on our nanofibers. Furthermore, it has been reported that increasing the amount of Ag + slows the rate of AuNP growth, which is consistent with the smaller AuNPs synthesized using the highest Ag + concentration (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…According to another mechanism, the reduction of Au ions to Au 0 leaves many Cl ions in solution. 66,67 In the presence of Ag ions, AgCl precipitates on the surface of the growing AuNPs, thereby blocking those surface sites. 68,69 The final result of both mechanisms is that certain Au surface sites are blocked from Au growth by precipitated Ag, either in the form of a Ag 0 monolayer or as AgCl, thus leading to the anisotropic in situ growth of the AuNPs on our nanofibers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Various strategies have been designed to fabricate diverse magneto-plasmonic nanostructures by growing Au shells over the MPs or by attaching isolated Au nanoparticles (Au NPs) onto the surface of MPs [37,[45][46][47][48][49][50]. The obtained nanocomposites exhibit the typical core-shell "gold-coated magnetic" nanostructures.…”
Section: Magneto-plasmonic Nanoparticles For Sensingmentioning
confidence: 99%